2003
DOI: 10.1136/tc.12.1.67
|View full text |Cite
|
Sign up to set email alerts
|

The importance of social sources of cigarettes to school students

Abstract: Objective: To discover the importance of social sources of tobacco to young people as opposed to commercial sources; to describe the peer market for cigarettes in schools and the consequences for young people of their involvement in it. Study design: Cross sectional questionnaire survey, one-to-one interviews, and focus groups. Setting: Seven schools in Birmingham, UK. Subjects: All students in two randomly selected classes from each school completed the questionnaire, and never smokers, occasional smokers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
49
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 7 publications
6
49
1
Order By: Relevance
“…40,41 These theories are typically applied to commerce within developing countries, 42,43 but also may be an appropriate model for understanding the sale of single cigarettes in Sandtown-Winchester. Previous research has applied theories of the informal economy to the exchange of cigarettes among school children when access to commercial sources was made increasingly restricted, 44 whereby markets emerged that were centered around so called Bvending peers^who recognized the economic opportunity for selling cigarettes to classmates. In our study, vendors tend not to be schoolchildren, nor necessarily young adults, but rather, people in the community with a need for cash to meet daily living needs (including, but not limited to, money for illicit drugs).…”
Section: Discussionmentioning
confidence: 99%
“…40,41 These theories are typically applied to commerce within developing countries, 42,43 but also may be an appropriate model for understanding the sale of single cigarettes in Sandtown-Winchester. Previous research has applied theories of the informal economy to the exchange of cigarettes among school children when access to commercial sources was made increasingly restricted, 44 whereby markets emerged that were centered around so called Bvending peers^who recognized the economic opportunity for selling cigarettes to classmates. In our study, vendors tend not to be schoolchildren, nor necessarily young adults, but rather, people in the community with a need for cash to meet daily living needs (including, but not limited to, money for illicit drugs).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the proportion of teens who buy cigarettes in stores have been even more diverse, varying from 6.6% of middle school students [11] to 89% of 12-to 19-year-olds [10]. Findings regarding vending machine use are similar: one study [12] found that no young teens acknowledged using machines, whereas 44% admitted use in another study [10].…”
mentioning
confidence: 85%
“…To further complicate matters, the number of response options presented has ranged from as few as three sources [21] to as many as 14 [12]. In fact, there does not appear to be any agreed-upon list of possible responses.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Schools provide a route for communicating with a large proportion of young people and more school-based programmes for smoking prevention are developed (35)(36)(37)(38). Cognitive and pharmacological therapy used for tobacco cessation among youth.…”
mentioning
confidence: 99%